ANALYSIS OF SOFTWARE FOR THE BEEF CATTLE MANAGEMENT UNDER THE PERSPECTIVE OF SOFTWARE QUALITY - JORGE, Daniel Manzano; MACHADO, João Guilherme de Camargo Ferraz (Revista Brasileira de Engenharia de Biossistemas, 2011)
This research aimed to evaluate administrative management softwares in the beef cattle industry, from the methodology proposed by Campos (2001). Specifically, the softwares were compared based in the quality attributes identified and ranked them in order to propose a ranking of the best offer. It was evaluated seven samples of software, assigning scores from 0 to 4 for each sub-characteristic, corresponding to a scale that ranged from total absence and total presence of each sub-characteristic. The results indicated that all the softwares evaluated showed good adequacy to some features, but they no longer meet the other questions considered relevant. It was concluded that the management software segment geared for the beef cattle industry does not answer fully to the sector and farmers have difficulties in choosing the products.